2020
DOI: 10.1080/22221751.2020.1721334
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of ST11-K47 and ST11-K64 hypervirulent carbapenem-resistant Klebsiella pneumoniae in bacterial liver abscesses from China: a molecular, biological, and epidemiological study

Abstract: Background: Multidrug-resistant bacteria, especially those with high virulence, are an emerging problem in clinical settings. Methods: We conducted a multicentre epidemiological and comparative genomic analysis on the evolution, virulence and antimicrobial resistance of carbapenem-resistant Enterobacteriaceae in patients with bacterial liver abscesses from 2012 to 2016. Results: A total of 477 bacterial isolates were collected. Enterobacteriaceae were the main pathogen (89.3%) with K. pneumoniae (52.4%) predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
68
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 33 publications
7
68
2
Order By: Relevance
“…K-type K64 was not only identi ed as the most predominant K-type, but also as the K-type associated with the highest case/fatality rates of CRKP infected patients (> 70 % in patients treated at the MHT ICU). This ts recent observations, both regarding the high case/fatality [6,7] as well as the increased virulence of capsule type K64 [29].…”
Section: Discussionsupporting
confidence: 87%
“…K-type K64 was not only identi ed as the most predominant K-type, but also as the K-type associated with the highest case/fatality rates of CRKP infected patients (> 70 % in patients treated at the MHT ICU). This ts recent observations, both regarding the high case/fatality [6,7] as well as the increased virulence of capsule type K64 [29].…”
Section: Discussionsupporting
confidence: 87%
“…As reported, [23][24][25] ST11 K pneumoniae clone is the dominant clone of KPC-producing K. pneumoniae in the world. ST11 clone would be good colonizers to capture plasmids and these isolates with ST11 clone will be easily transmitted between patients.…”
Section: Discussionmentioning
confidence: 93%
“…Strain KP20194d, isolated from patient 4, and strain KP20194c, isolated from patient 3, shared the loss of a 10-kbp fragment from plasmid p2 which contained rmtB (Figures 1, 2), suggesting the transmission from patient 3 to patient 4 given the timeline and the use of the same bed and ventilator. The emergence of the CR-hvKP strains can result from the acquisition of either a carbapenemase-producing plasmid by a hypervirulent strain, usually belonging to serotype ST23 and capsular type K1/K2 (Yao et al, 2015;Dong et al, 2019;Shen et al, 2019); or a pLVKP-like virulence plasmid by CRKP strains, among which ST11 is dominant in China (Wei et al, 2016;Ruan et al, 2020;Yang et al, 2020). Our strains likely fit into the latter category, because MLST and Kaptive software analyses indicated that our 13 strains belonged to ST11-K64, and also because of the existence of the pLVPK-like virulence plasmid (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…When the landmark convergence of CR-hvPK was originally reported, the strains referred to were K47 ( Gu et al, 2018 ). Moreover, when Yang et al (2020) reported the emergence of ST11-K47/K64 CR-hvKP, the authors stated that ST11-K64 was relatively rare. However, a subsequent retrospective multicenter study showed that ST11-K64 must have been spreading in China for several years and represents the most common type of CR-hvKP ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%